Initial Elastic Stiffness of Bolted Shear Connectors in Steel-Concrete Composite Structures - Chenggong Wang; Diankai Cao; Xiaoyang Liu; Yucai Jing; Wenzhuo Liu; Guotao Yang (Advances in Civil Engineering)
Bolted shear connectors have the advantages of being easily fitted and dismantled during construction, the initial elastic stiffness of which has a great influence on the structural performance of the connected composite structures. In this paper, the initial elastic behaviors of three types of bolted shear connectors used in steel-concrete composite structures (i.e., the bolt with nonembedded nut, the bolt with single-embedded nut, and the bolt with double-embedded nuts) are investigated using finite element analysis (FEA). After the FE models are verified against the experimental results in other literature, an extensive parametric study is carried out to investigate the effects of eight parameters of the composite structures on the initial shear stiffness and tension stiffness as well as coupling stiffness. Empirical formulas are subsequently developed for obtaining the initial elastic stiffness of the bolted shear connectors, based on which further FEA is performed. The FEA results are in good agreement with the experimental results, illustrating the effectiveness of the empirical formulas.